Stages of Hypertension Correlate with Hemiparesis in Primary Intracerebral Hemorrhage Adult Patients - Nabeel Usama Okbah; Viskasari P. Kalanjati; Asra Al Fauzi; Nurina Hasanatuludhhiyah (Wolters Kluwer - Medknow Publications, 2023)
Introduction: Intracerebral hemorrhage (ICH) is one of the leading causes of mortality and morbidity in Indonesia, with only a small portion achieving long-term independence. Many studies in the last decade have recognized hypertension as one of the main causes of primary ICH. Moreover, it is associated with poor outcomes, the most common of which is hemiparesis. In this study, we aim to analyze the correlation between stages of hypertension and hemiparesis among ICH patients admitted to Dr. Soetomo General Academic Hospital in Surabaya. Methods: We conducted a cross-sectional study on adult patients with primary ICH admitted to the Emergency Department in 2020 and analyzed the medical record data on the initial blood pressure and presentation of hemiparesis. Results: Eighty-seven ICH patients were recorded, with a mean age of 57.0 ± 10.4 years. The majority of these patients were male (60.9%). Hemiparesis was found in 58 patients (66.7%), and the blood pressure of 73 patients was classified under Stage 1 hypertension, Stage 2 hypertension, or hypertensive crisis. Fisher's exact test revealed a significant correlation between stages of hypertension and hemiparesis (P = 0.012). Furthermore, binary logistic regression demonstrated that the odds ratio of hemiparesis associated with hypertension is 4.77 times more likely to occur compared to nonhypertensive ICH patients. Conclusion: Our study showed that stages of hypertension significantly correlate with hemiparesis, leading to poor functional outcomes among adult patients with primary ICH.